Increasing Incidence of Colorectal Cancer in Adolescents and Young Adults Aged 15–39 Years in Western Australia 1982–2007: Examination of Colonoscopy History - Troeung, Lakkhina; Sodhi-Berry, Nita; Martini, Angelita; Malacova, Eva; Ee, Hooi; O’Leary, Peter; Lansdorp-Vogelaar, Iris; Preen, David B. (Frontiers in Public Health, 2017)
Aims: To examine trends in colorectal cancer (CRC) incidence and colonoscopy history in adolescents and young adults (AYAs) aged 15-39 years in Western Australia (WA) from 1982-2007. Design: Descriptive cohort study using population-based linked hospital and cancer registry data. Method: Five-year age-standardised and age-specific incidence rates of CRC were calculated for all AYAs and by sex. Temporal trends in CRC incidence were investigated using Joinpoint regression analysis. The annual percentage change (APC) in CRC incidence was calculated to identify significant time trends. Colonoscopy history relative to incident CRC diagnosis was examined and age and tumour grade at diagnosis compared for AYAs with and without pre-diagnosis colonoscopy. CRC-related mortality within five and ten years of incident diagnosis were compared for AYAs with and without pre-diagnosis colonoscopy using mortality rate ratios (MRR) derived from negative binomial regression. Results: Age-standardised CRC incidence among AYAs significantly increased in WA between 1982-2007, APC=3.0 (95% CI 0.7-5.5). Pre-diagnosis colonoscopy was uncommon among AYAs (6.0%, 33/483) and 71% of AYAs were diagnosed after index (first ever) colonoscopy. AYAs with pre-diagnosis colonoscopy were older at CRC diagnosis (mean 36.7±0.7 years) compared with those with no prior colonoscopy (32.6±0.2 years), p < 0.001. At CRC diagnosis, a significantly greater proportion of AYAs with pre-diagnosis colonoscopy had well-differentiated tumours (21.2%) compared with those without (5.6%), p=0.001. CRC-related mortality was significantly lower for AYAs with pre-diagnosis colonoscopy compared to those without, for both 5-year (MRR=0.44, [95%CI 0.27-0.75], p=0.045) and 10-year morality (MRR=0.43 [95%CI 0.24-0.83], p=0.043). Conclusion: CRC incidence among AYAs in WA has significantly increased over the 25-year study period. Pre-diagnosis colonoscopy is associated with lower tumour grade at CRC diagnosis as well as significant reduction in both 5- and 10-year CRC-related mortality rates. These findings warrant further research into the balance in benefits and harms of targeted screening for AYA at highest risk.